2015
DOI: 10.3892/br.2015.448
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of visual and anatomical outcomes for neovascular age-related macular degeneration treated with bevacizumab

Abstract: Abstract. The present study aimed to evaluate the predictive factors for visual and anatomical outcomes in neovascular age-related macular degeneration (AMD) patients treated with intravitreal bevacizumab (IVB). A total of 113 patients with neovascular AMD received IVB treatment. The best corrected visual acuity (BCVA), central retinal thickness (CRT) and total macular volume (TMV) were assessed before the injection, and at 1, 2, 3 and 9 months after surgery. Changes in BCVA and these optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(25 reference statements)
0
6
0
Order By: Relevance
“… 40 , 41 Specifically, both in patients with classic CNV and in those with baseline CRT >300 μm, the CRT decrease from baseline to 6 months post-baseline nearly reached (49.59 μm for the classic CNV subgroup) or exceeded (53.75 μm for those with baseline CRT >300 μm) the 50 μm cut-off used to define a clinically relevant significant reduction in a previous study. 41 …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“… 40 , 41 Specifically, both in patients with classic CNV and in those with baseline CRT >300 μm, the CRT decrease from baseline to 6 months post-baseline nearly reached (49.59 μm for the classic CNV subgroup) or exceeded (53.75 μm for those with baseline CRT >300 μm) the 50 μm cut-off used to define a clinically relevant significant reduction in a previous study. 41 …”
Section: Discussionmentioning
confidence: 84%
“…Notably, in ELEVATE, greater decreases in CRT were found to be associated with the presence of classic versus occult CNV and greater baseline CRT (>300 μm), with the latter reported as a predictor of anatomical outcomes in other studies as well. 40,41 Specifically, both in patients with classic CNV and in those with baseline CRT >300 μm, the CRT decrease from baseline to 6 months post-baseline nearly reached (49.59 μm for the classic CNV subgroup) or exceeded (53.75 μm for those with baseline CRT >300 μm) the 50 μm cut-off used to define a clinically relevant significant reduction in a previous study. 41 Regarding visual acuity assessments, a statistically significant median gain of 3.2 letters was found in ELEVATE at 6 months post-baseline, with 17% of the eyes experiencing clinically meaningful increases of ≥15 letters, 37.5% gaining ≥5 letters, and 82% having stable or improved BCVA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… 34 , 35 Many prospective randomized clinical trial data have shown that the use of VEGF inhibitors – such as ranibizumab and bevacizumab (Avastin) – is an effective treatment for retinal vascular diseases. 35 37 Despite the success of drugs in the treatment of DR, the exact mechanisms have only been partly resolved. Previous studies have revealed that VEGF-A is the best-studied inducer of ocular angiogenesis and vascular permeability and is crucial for the further development of early DR. 38 40 STZ-induced diabetes in rats is a widely used model to study the signs of early DR.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Chinese patients with nAMD receiving anti-VEGF treatment (N = 113), there was a moderate correlation 58 between change from baseline to month 9 in CRT measured with SD-OCT and BCVA measured in logMAR units (Pearson correlation coefficient of 0.34). 60 In a prospective cohort study (N = 1,142) within the Comparison of AMD Treatments Trials (CATT), a non-linear relationship was observed between TD-OCT-measured CRT and visual acuity assessed with a computerized version of the ETDRS. 61 In pooled data taken from 4, 12, and 24 weeks after initiation of treatment, eyes with CRT of less than 120 µm or greater than 212 µm had worse visual acuity than eyes with a CRT in the range of 120 µm to 212 µm (i.e., the range of values within 2 standard deviations of the mean measured for healthy eyes).…”
Section: Early Treatment Diabetic Retinopathy Study Chartsmentioning
confidence: 99%